Match intensity and heart rate predictors in top level basketball referees during men`s Eurobasket - Vaquera, A.; Mielgo-Ayuso, J.; Calleja-Gonzalez, J.; Leicht, A S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aims of this study were to determine the heart rate (HR) response of referees during men's Eurobasket Championship and identify relationships body composition and other match variables as predictor of HR.